MENINGIOMA DI FORAMEN MAGNUM - Yossi Maryanti*, Basjiruddin Ahmad**, Syarif Indra** (Neurona Majalah Kedokteran Neuro Sains, 2011)
43YEAROLD FEMALE PATIENT HOSPITALIZED WITH WEAKNESS OF BOTH EXTREMITIES AND LOSS OF SENSE AT LOWER MIDLLE NECK ACCOMPANYING OCCIPITAL HEADACHE ON PHYSICAL EXAMINATION WE FOUND TETRAPARESIES AND HYPESTESIA AT LOWER DERMATOMES THORACAL III MRI REVEAL A MASS WITH SIZE 3X2 CM IN THE FORAMEN MAGNUM THE DIAGNOSIS IS ESTABLISHED AS A FORAMEN MAGNUM MENINGIOMA IN PATIENT WE HAVE DONE TUMOR RESECTION BY POSTEROLATERAL APPROACHON HISTOPATHOLOGICAL WE FOUND TRANSITIONAL MENINGIOMA